Heroes. Season 4 [videorecording (DVD)] - Kring, Tim, 1957- (Heroes, 2010)
As the Heroes mourn fallen friends and face dangerous new foes, prepare for a wild ride filled with shocking twists and turns, through an ominous funhouse that culminates in a brave new world.